Eating in the lockdown during the Covid 19 pandemic; self-reported changes in eating behaviour, and associations with BMI, eating style, coping and health anxiety. (1st June 2021) - Coulthard, Helen; Sharps, Maxine; Cunliffe, Louise; van den Tol, Annemieke
Abstract: The global coronavirus pandemic (Covid 19) resulted in national lockdowns where individuals were asked to isolate in their homes to stop the spread of the disease. Using a cross-sectional survey, the current paper aimed to examine self-reported changes in eating patterns and behaviour during the lockdown in the UK, and associations with BMI, demographic variables, eating styles, health anxiety, food insecurity and coping strategies. Participants ( N = 620) were recruited online through social media advertising. The results showed that there were self-reported changes to food consumption during the lockdown across the sample. Increases in consumption of HED (high energy density) snack foods during the lockdown was associated with sex, pre-lockdown eating behaviour (emotional eating and uncontrolled eating), and Covid-specific health anxiety. Increases in positive eating practices such as eating more home prepared foods, and fruits and vegetables, were associated with adaptive coping strategies. Higher emotional eating (EE) during the lockdown was associated with a higher BMI, higher pre-lockdown EE and maladaptive coping strategies. Maladaptive coping strategies moderated the relationship between BMI and EE during the lockdown. In particular a higher BMI was associated with higher EE during the lockdown if an individual also had higher maladaptive coping strategies. These findings suggest that changes to eating behaviour may be part of a wider style of maladaptive or adaptive coping, particularly in those with a history of EE or uncontrolled eating. Preparing individuals to adopt more adaptive coping strategies during lockdown situations may be crucial to improving health during subsequent the lockdown events.